PRAKIRAAN KEBUTUHAN ENERGI LISTRIK WILAYAH JAWA-BALI TAHUN 2017-2036 DENGAN GABUNGAN METODE ANALITIS, EKONOMETRI, DAN KECENDERUNGAN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2017)
Electricity is one of the energy required because it can be converted into other energy forms and easier in terms of distribution. Along with the growth of population and economic growth are rising rapidly, demand of power also increases. Therefore, it needs distribution of electric power supply, in terms of technical and economic.In Indonesia, the use of electrical energy per capita is still low compared with the use of electrical energy per capita in other countries. Therefore, it needs to increase the use of electrical energy in order to approach the electrical energy per capita that is ideal with equitable distribution of electrical energy supply. In this study, the growth of electricity demand forecasts using the combined method consisting of analytical methods, econometrics and trends on sectoral approaches. From the results of electricity demand forecasts, from 2017 until 2036 electricity demand will increased 6,4% each year which dominated by household sector in 38,49%, industrial sector 36,62%, commercial sector 19,35%, and public sector 5,54%.To fulfillment the growth in electricity demand, it is necessary to supply additional power.